Membangun Personal Branding Dan Manajemen Waktu Di Kalangan Siswa SMP Melalui Konten TikTok Interaktif - Aji, Bima Tresna; Shalahuddin, Ahmad; Salsabila, Najwa; Sophia, Nadya Rahma; Jayanti, Rabita Putri; Putri, Jesica Khristianti (Penerbit Widina, Widina Media Utama, 2025)
Advances in digital technology have drastically changed the way teenagers communicate and build their identities. One of the popular social media platforms among students is TikTok, which can be used as a tool for education and self-improvement. Objective: This community service activity aims to improve junior high school students’ understanding of the concepts of personal branding, time management, and the positive use of social media. Method: The implementation of this activity is educational socialization conducted through interactive presentations and group discussions, accompanied by assessments using pre-tests and post-tests in essay format, the number of participants in this socialization activity was 183 9th grade students of SMP Negeri 4 Sungai Raya. Results: From the results of the delivery of materials and the provision of post-test questions, there was an increase in students’ understanding of the aspects discussed, students in grades 9A-9B experienced an increase of 20%, students in grades 9C-9D experienced an increase of 51%, while students in grades 9E-9F experienced an increase of 48%. From the results of the activity, there was an increase in students’ understanding and knowledge regarding personal branding, content, and time management. ABSTRAKKemajuan dalam teknologi digital telah secara drastis mengubah cara komunikasi dan cara anak remaja membangun identitas mereka. Salah satu platform media sosial yang terkenal di kalangan siswa adalah TikTok, yang bisa digunakan sebagai alat pendidikan dan peningkatan diri. Kegiatan pengabdian ini bertujuan untuk meningkatkan pemahaman siswa SMP mengenai konsep personal branding, manajemen waktu, serta penggunaan media sosial secara positif. Cara pelaksanaan kegiatan ini adalah sosialisasi pendidikan yang dilakukan melalui presentasi interaktif dan pembicaraan kelompok, disertai dengan penilaian menggunakan pre-test dan post-test dalam format esai, jumlah peserta dari kegiatan sosialisasi ini sebanyak 183 siswa kelas 9 SMP Negeri 4 Sungai Raya. Dari hasil penyampaian materi dan pemberian soal post-test, terjadi peningkatan terkait pemahaman siswa terhadap aspek yang dibahas, siswa-siswi kelas 9A-9B mengalami peningkatan sebesar 20%, siswa -siswi kelas 9C-9D mengalami peningkatan sebesar 51%, sedangkan para siswa-siswi kelas 9E-9F mengalami peningkatan sebesar 48%. Dari hasil kegiatan terjadi peningkatan pemahaman dan pengetahuan para siswa terkait personal branding, konten, dan manajemen waktu.